Effect of problem-solving based methods on critical thinking and academic achievement of math among students of saravan higher education centers - Nosrat, Azizollah; Parsafar, Abdulhamid (International Journal of Applied Mathematical Research, 2017)
The aim of the present study is to determine the impact of problem-solving based methods on critical thinking and academic achievement of math in students of higher-education centers in the second semester of academic year 2013-14, Saravan city. The research method in this study is quasi-experimental, with the control group as well as pre-test and post-test. The study population includes all students in the second semester of 2013-14 who studied math in higher-education centers of Saravan city whose number was 400 and 130 students were selected as statistical samples. Measuring instruments used in this study were a researcher made academic achievement of math test and Watson-Glaser critical thinking test. To give an approximation of the content validity of the tests, analyzing books contents and comparing it with the extent of usage for conceptual questions, tests content validity was assured to some extent. The reliability of the test was calculated using bi-section method that according to the figures obtained for pre-test and post-test respectively (r = 0.71 and 0.68), tests have an acceptable and relatively high reliability. To analyze the data, t-test was used. The results showed that academic achievement of math and critical thinking in the test group, compared to the control group were higher and the differences between their means were significant.
Keywords: Academic Achievement of Math; Critical Thinking; Mathematics; Problem-Solving Based Methods.